Efektifitas Pijat Bayi Terhadap Durasi Menyusui Pada Bayi Usia 0-6 Bulan - Situmorang, Cory Chorajon; Sri Artina Dewi, Ni Nyoman; Kristina (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2022)
Infant massage is a technical method in midwifery care for neonates, infants and toddlers that can increase the frequency and duration of breastfeeding so that baby will feel comfortable and calm while breastfeeding. The aim of study was to determine the effectiveness of infant massage on the quality of breastfeeding in infants aged 0-6 Month at the Mariat District Health Center Sorong Years 2022. Research Design One group pre test-post test design using 30 sampel of infant aged 0-6 Month at the Mariat Health Center, Sorong Regency. Given treatment in the form of baby massage for 2 weeks. The results showed that there was an effectiveness of infant massage against Quality of Breastfeeding in infants aged 0-6 month at the Mariat Health Center (p 0.000 < 0.05). It is better not to schedule the baby to breastfeed because if it is scheduled will affect the production and subsequent release of breast milk, give breast milk whenever the baby wants to breastfeed.